2021
DOI: 10.21203/rs.3.rs-543999/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex differences in a cohort of COVID-19 Italian patients hospitalized during the first and second pandemic waves.

Abstract: Background: Coronavirus Disease 2019 (COVID-19) severity seems to be influenced by genetic background, sex, age, and presence of specific comorbidities. So far, little attention has been paid to sex-specific variations of demographic, clinical and laboratory features of COVID-19 patients referred to the same hospital in the two consecutive pandemic waves.Methods: Demographic, clinical and laboratory data were collected in 1,000 COVID-19 patients (367 females and 633 males), 500 hospitalized in the first wave a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
(32 reference statements)
1
0
0
2
Order By: Relevance
“…Despite the fact that comorbidities significantly contribute to the development of more severe clinical conditions as well as death, their percentage was comparable in both groups, thus the significant difference in mortality between males and females is not due to their preexisting medical conditions. Similar observations were made in different studies in Italy, USA and China (32)(33)(34), further supporting our finding that SARS-CoV-2 infected males are more at risk for worse outcomes and death. A meta-analysis revealed that age had a significant impact on the COVID-19 patient mortality, with an important cut-off point at age >50 and particularly >60 (35).…”
Section: Haplotype Lineagesupporting
confidence: 92%
“…Despite the fact that comorbidities significantly contribute to the development of more severe clinical conditions as well as death, their percentage was comparable in both groups, thus the significant difference in mortality between males and females is not due to their preexisting medical conditions. Similar observations were made in different studies in Italy, USA and China (32)(33)(34), further supporting our finding that SARS-CoV-2 infected males are more at risk for worse outcomes and death. A meta-analysis revealed that age had a significant impact on the COVID-19 patient mortality, with an important cut-off point at age >50 and particularly >60 (35).…”
Section: Haplotype Lineagesupporting
confidence: 92%
“…Welle und hatten weniger Komorbiditäten [8]. In Italien war das Durchschnittsalter in der zweiten Welle signifikant höher und die Zahl der männlichen Patienten mit mehreren Symptomen war höher als die der weiblichen [9]. In den Niederlanden änderten sich die Merkmale der Patienten hinsichtlich Alter, Geschlecht und Körpergewicht nicht.…”
Section: Conclusion Patientsʼ Characteristics Did Not Vary In Germanyʼsunclassified
“…Welle. Dies steht im Einklang mit der Studie aus Hamburg [11] und den Daten aus Colmar, Frankreich [15], aber im Gegensatz zu anderen internationalen Berichten [8,9]. Bestimmte Komorbiditäten, die mit einem erhöhten Risiko für Krankenhausaufenthalte oder schwere Verläufe von COVID-19 einhergehen, wurden bereits in der 1.…”
Section: Diskussionunclassified